Genotypic variations in the dynamics of metal concentrations in poplar leaves: A field study with a perspective on phytoremediation. (April 2015) - Pottier, Mathieu; García de la Torre, Vanesa S.; Victor, Cindy; David, Laure C.; Chalot, Michel; Thomine, Sébastien
Abstract: Poplar is commonly used for phytoremediation of metal polluted soils. However, the high concentrations of trace elements present in leaves may return to soil upon leaf abscission. To investigate the mechanisms controlling leaf metal content, metal concentrations and expression levels of genes involved in metal transport were monitored at different developmental stages on leaves from different poplar genotypes growing on a contaminated field. Large differences in leaf metal concentrations were observed among genotypes. Whereas Mg was remobilized during senescence, Zn and Cd accumulation continued until leaf abscission in all genotypes. A positive correlation between Natural Resistance Associated Macrophage Protein 1 ( NRAMP1 ) expression levels and Zn bio-concentration factors was observed. Principal component analyses of metal concentrations and gene expression levels clearly discriminated poplar genotypes. This study highlights a general absence of trace element remobilization from poplar leaves despite genotype specificities in the control of leaf metal homeostasis. Highlights: Poplar genotypes display large variations in leaf metal concentrations. Trace elements are not remobilized during poplar leaf senescence. Distinct transporter genes control metal homeostasis at different leaf stages. Poplar genotypes use distinct mechanisms to control leaf metal homeostasis. NRAMP1 metal transporter could contribute to Zn and Cd accumulation in poplar leaves. Abstract : In order to improve metal phytoextraction using poplars, this work provides new insights on the control of leaf metal concentrations through principal component and correlative analyses.